Natural convection in right-angle porous trapezoidal enclosure partially cooled from inclined wall - Varol, Yasin; Öztop, Hakan Fehmi; Pop, Ioan (Pergamon-Elsevier Science Ltd, 2009)
A numerical study is conducted to investigate the steady free convection flow in a two-dimensional right-angle trapezoidal enclosure filled with a fluid-saturated porous medium. The left vertical wall of the cavity is heated; the inclined wall is partially cooled; and the remaining walls are insulated (adiabatic). Three different cases are considered. While in Case I the cooler wall is located adjacent to the top wall, in Case 11 it is located in the middle inclined wall. In Case III, it is located adjacent to the bottom wall. Flow and heat transfer characteristics are studied for a range of parameters: the Rayleigh number, Ra, 100 <= Ra <= 1000; and the aspect ration, AR=0.25, 0.50 and 0.75. Numerical results indicate that there exist significant changes in the flow and temperature fields as compared with those of a differentially heated square porous cavity. These results lead, in particular, to the prediction of a position of minimum heat transfer across the cavity, which is of interest in the thermal insulation of buildings and other areas of technology. (C) 2008 Elsevier Ltd. All rights reserved.
Keywords: Natural convection; Porous medium; Partially cooled; Trapezoidal enclosure